Profil of Implementation of Post Exposure Prophylaxis of Hepatitis B, Hepatitis C and Human Immunodeficiency Virus to Health Care Worker in Cipto Mangunkusomo Hospital 2014-2016 - Ratih, Dewi Mira; Yunihastuti, Evy; Lestari, Regina; Sulaiman, Andri Andri; Rinaldi, Ikhwan (Jurnal Penyakit Dalam Indonesia, 2019)
Introduction. Health care workers (HCW) have a high risk of infectious substance exposure. Hepatitis B, hepatitis C, or human immunodeficiency virus (HIV) are some diseases transmitted by body fluid or body tissue. Cipto Mangunkusumo Hospital Jakarta has been implementing post-exposure prophylaxis (PEP)s towards HIV, hepatitis B, and hepatitis C. This study aimed to identify the implementation of post-exposure prophylaxis of HIV, Hepatitis B, and Hepatitis C among HCW in Cipto Mangunkusumo Hospital Jakarta. Methods. A cross-sectional study was conducted to exposed workers in Cipto Mangunkusumo Hospital Jakarta between 2014-2016 who had been recorded by report. Demographic data were collected through medical record and interview was conducted to gather additional data. Statistical analysis was conducted with SPSS 20. Results. Among 196 reports, most HCW were female (69.9%), worked as nurse (38.3%), medical doctor (49.5%), and exposed percutaneously (93.4%). There were 183 risky exposures, with 19 (10.4%) reactive anti-HIV, 11 (6.0%) positive HBsAg, and 12 (6.6%) reactive anti-HCV in source of exposure. Almost all of the HCW has no HIV, hepatitis B, nor hepatitis C at the moment of exposure. Recommendation for antiretroviral (ARV) was given to 81 HCW, but only 49.4% completed the course. Anti-HIV follow up was done only by 21.3% workers. Recommendation of PEP for hepatitis B was given to 37 HCW. But, only 13.5% and 13.3% receive hepatitis B vaccination and hepatitis B immunoglobulin, respectively. Follow-up of HBsAg and anti-HBs on 3rd and 6th months were done by 41 (31.1%), 38 (28.8%), and 2 (1.5%) workers who were recommended to receive prophylaxis. In 182 workers recommended to do the follow-up of anti-HCV, 39 (21.4%), and 37 (20.3%) workers did the follow-up on 3rd and 6th month. Majority of exposed workers were not re-evaluated for HBsAg (64.9%) and anti-HCV (69.9%). Conclusions. The implementation of post-exposure prophylaxis for HIV, Hepatitis B, and Hepatitis C was still low especially in re-evaluation serologic marker. Comprehensive management is recommended including improving knowledge of health care workers, re-evaluation of operational procedure standard, and effective communication.